IMPROVING MUFRODAT MASTERY THROUGH AUDIOVISUAL MEDIA-BASED TEACHING MATERIALS IN ARABIC LANGUAGE LEARNING AT JUNIOR HIGH SCHOOL - Mawardi Mawardi; Aisyah Arjuna; Hasriadi Hasriadi; Asgar Marzuki (Edukasi Islami : Jurnal Pendidikan Islam, 2022)
Audiovisual media can help students in improving their mastery of mufrodat. Mufrodat learning is a process of delivering learning in the form of words or vocabulary in Arabic learning. This study aims to improve the mastery of Mufrodat through the application of teaching materials based on audiovisual media. The study involved an Arabic teacher and 27 learners. This research uses classroom action research with the Kemmis & McTaggart model, which has four cycle stages: planning, implementation, observation or observation, and reflection. Each cycle consists of two meetings. The data collection techniques used are observation, tests and documentation. The results of this study show that: 1) The application of Audiovisual media in improving the mastery of mufrodat students of grade VII SMP Muhammadiyah Boarding School Palopo can be carried out correctly. The results of observations of student learning activities during the learning process evidence it. 2) The mastery of mufrodat students in grade VII of SMP Muhammadiyah Boarding School Palopo before and after the application of audiovisual media has increased with each cycle.